A new probabilistic approach to estimating marine gastropod densities from baited traps. (29th July 2018) - Coston‐Guarini, Jennifer; Guarini, Jean‐Marc; Boehm, Frederike Ricarda; Kerkhove, Thomas R. H.; Rivera, Frances C.; Erzini, Karim; Charles, François; Deprez, Tim; Chauvaud, Laurent
Abstract: A new probabilistic approach is proposed to assess muricid species population abundances at scales relevant to both Ancient and Modern coastal fisheries. Motivated by the long‐term goal of reconstructing the dynamics of exploited murex populations during Antiquity, the objective was to estimate the population density of the banded dye‐murex, Hexaplex trunculus (Linnaeus, 1758) from successive captures with baited traps, using a method similar to the technique employed in the Mediterranean purple dye industry. The stochastic model developed simulates cumulative captures while accounting for high variability. It was calibrated with data acquired during a field trapping experiment (Crete Island, Greece). Traps' catchability and Effective Area of Attraction (EAA) were estimated using the individual speed and behavioural response towards bait from laboratory experiments. Average density of H. trunculus was estimated as 2.2 ± 1.4  SE individuals per square metre, with no significant differences between seagrass and rocky habitats. The clearing time of successive capture experiments averaged 84 ± 6  SE hr. Clearing ca . 0.4 ha of subtidal area would be necessary to produce ca . 1.0 g of pure Tyrian purple pigment. The method described is generalizable to making population abundance estimates for similar groups, such as whelks, in modern fisheries.